How to launch a magazine in this digital age - Hogarth, Mary 1968- (Bloomsbury, 2014)
"Lively and engaging, How to Launch a Magazine in this Digital Age adopts a practical guide students or inexperienced editors to the process of setting up and launching a new publication -- be it digital, print or a combination of both. Using case studies, theoretical/critical insights, and tests/exercises, this is the first how-to to embrace digital technologies, including a companion website with additional support with podcasts, web links, forums and timed live author chats. The key to the text's success is its ability to encompass the complete process. It begins with the initial idea and follows the process through to developing a business plan as well as setting an editorial strategy to achieve and maintain an audience in a digital age -- where traditional print formats face an uncertain future. It includes checklists and realistic timescales for producing a digital/print magazine, for both the working professional and the student in the classroom setting"-- Provided by publisher.